KAJIAN KRIMINOLOGI TERHADAP TAWURAN YANG BERPOTENSI TINDAK PIDANA OLEH PELAJAR DI KOTA PADANG - Rahmat, Budi; Fitriati, Fitriati (UNES Law Review, 2019)
Various efforts were made by the regional government and law enforcement officials to tackle brawls between students in the city of Padnag, but there was no formulation of countermeasures that could eradicate fights between students in the city of Padang. This research is a legal research with analytical descriptive specifications with a normative juridical approach supported by an empirical juridical approach. The results showed that the causes of brawls among adolescents who have the potential for criminal acts in the city of Padang include internal factors, which are quite low self-control, lack of religious values ​​in themselves and want to see their existence. Furthermore External Factors include egoistic community, because of friend's invitation, because of a sense of solidarity, because of school selfishness and because of pressure and invitation from school alumni. Efforts made to combat the occurrence of fights between adolescents who have the potential for criminal acts in the city of Padang include preventive efforts, including through family channels such as supervision and family attention to other family members, school paths in the form of lightning pesantren, character and other education etc. and routine supervision. Repersive measures such as School actions to provide disciplinary penalties, legal processes by the police and conduct acts of arrest and coaching by the Civil Service Police Unit.